2021
DOI: 10.1016/j.devcel.2021.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable P body physical states differentially regulate bicoid mRNA storage during early Drosophila development

Abstract: Summary Ribonucleoprotein condensates can exhibit diverse physical states in vitro and in vivo . Despite considerable progress, the relevance of condensate physical states for in vivo biological function remains limited. Here, we investigated the physical properties of processing bodies (P bodies) and their impact on mRNA storage in mature Drosophila oocytes. We show that the conserved DEAD-box RNA helicase M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 117 publications
2
53
0
Order By: Relevance
“…Many GFP-Me31B foci were detected in the cytoplasm of early nc14 embryos (Figs 5A and S10A). These foci have a mean radius of 200 nm (S10B Fig), consistent with a previous observation that P-bodies in the embryo are smaller than those in the oocyte [55].…”
Section: Plos Biologysupporting
confidence: 90%
“…Many GFP-Me31B foci were detected in the cytoplasm of early nc14 embryos (Figs 5A and S10A). These foci have a mean radius of 200 nm (S10B Fig), consistent with a previous observation that P-bodies in the embryo are smaller than those in the oocyte [55].…”
Section: Plos Biologysupporting
confidence: 90%
“…Many GFP-Me31B foci were detected in the cytoplasm of early nc14 embryos (Figure 5A, Figure S9A). These foci have a mean radius of 200 nm (Figure S9B), consistent with a previous observation that P-bodies in the embryo are smaller than those in the oocyte (Sankaranarayanan et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…We speculate that P-bodies are involved in both storage and degradation in an mRNA dependent manner, with features of an individual mRNA as well as the proteins present in P-bodies at a particular developmental time influencing which function dominates. In support of this, it is known that there are changes in P-bodies during Drosophila development, for example from being large and viscous in the mature oocyte to smaller, more dynamic structures in the early embryo (Sankaranarayanan et al, 2021). Moreover, at the maternal-to-zygotic transition some P-body proteins are degraded, including the Cup translational repressor protein, which may facilitate a switch from a translational repression/storage role to an mRNA degradation function prevailing in P-bodies (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Tudor domain has been shown to promote aggregate formation through sDMA binding in mammalian cells (Courchaine et al 2021), implying the importance of molecular association by Tdrds for nuage formation. Recent studies have shown that membrane-less organelles composing RNA and proteins are responsible for diverse RNA processing including P-body and Yb body in Drosophila, modulating their molecular organization called phase separation (Kistler et al 2018; Hirakata et al 2019; Sankaranarayanan et al 2021). Two of Tdrd proteins localized at Drosophila nuage, Tej and Tap, contain an additional conserved Lotus domain that is found in bacteria to eukaryotes (Kubíková et al 2021).…”
Section: Introductionmentioning
confidence: 99%